Seeds of change: training restoration practitioners to solve genetic problems - Jalonen, R. (Bioversity International and the International Center for Tropical Agriculture, 2016)
This post explains why training for planning implementation and monitoring of ecosystem restoration is critical to improve the effectiveness of restoration programmes and meet related global commitments including Aichi Targets 14 and 15. This is the fourth blog in the CBD COP13 Forest and Landscape Restoration Blog Series highlighting why mainstreaming agricultural and tree biodiversity in sustainable food and production systems is critical to achieve the CBD's Strategic Plan for Biodiversity, with a particular focus on forest and landscape restoration.